2015
DOI: 10.3389/fmed.2015.00051
|View full text |Cite
|
Sign up to set email alerts
|

microRNA: Diagnostic Perspective

Abstract: Biomarkers are biological measures of a biological state. An ideal marker should be safe and easy to measure, cost efficient, modifiable with treatment, and consistent across gender and ethnic groups. To date, none of the available biomarkers satisfy all of these criteria. In addition, the major limitations of these markers are low specificity, sensitivity, and false positive results. Recently identified, microRNAs (miRNAs) are endogenous, evolutionarily conserved small non-coding RNA (about 22–25 nt long), al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 101 publications
0
51
0
3
Order By: Relevance
“…These molecules are responsible for the regulation of various physiological processes and alterations in their expression levels can reflect different pathological conditions. Moreover, miRNAs are stable, and they can be quantified by different molecular techniques (32,33), such as qRT-PCR (33,34). Due to their diagnostic potential, miRNAs were evaluated as biomarkers in several pathological conditions like infectious diseases (38,39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These molecules are responsible for the regulation of various physiological processes and alterations in their expression levels can reflect different pathological conditions. Moreover, miRNAs are stable, and they can be quantified by different molecular techniques (32,33), such as qRT-PCR (33,34). Due to their diagnostic potential, miRNAs were evaluated as biomarkers in several pathological conditions like infectious diseases (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs have also been identified as endogenous molecules with differential expression profiles under pathological conditions. Due to their characteristic and stability, they have been suggested as potential disease biomarkers (31,32).…”
mentioning
confidence: 99%
“…Studies have shown that miRNAs appear to be the most important biomarker for acute and prognostic disease assessment as well as therapeutic agents for cardiovascular diseases. It is believed that miRNAs could be used as highly sensitive early diagnostic biomarkers and therapeutic targets for many cardiovascular diseases such as atherosclerosis, acute myocardial infarction, heart failure, hypertension and stroke as well as cancer, and was reviewed and published recently [26, 71]. In heart failure patients, miRNA-423-5p is highly expressed in the blood irrespective of age and gender and might be a sensitive biomarker for heart diseases [83].…”
Section: Mirna In Diagnosis and Their Clinical Applicationsmentioning
confidence: 99%
“…MicroRNAs have the potential to become accurate, easily measurable biomarkers, with features fortuitous for diagnostic testing methods, such as stability in FFPE tissue, blood and perhaps other bodily fluids (21).…”
Section: Patients Below Patients Abovementioning
confidence: 99%